Identification of a novel pyridine derivative with inhibitory activity against ovarian cancer progression in vivo and in vitro - Si, Lulu; Lai, Tianjiao; Zhao, Junru; Jin, Yuxi; Qi, Meng; Li, Mingyue; Fu, Hanlin; Shi, Xiaojing; Ma, Liying; Guo, Ruixia (Frontiers in Pharmacology, 2022)
Ovarian cancer is the second leading cause of death of female gynecological malignant tumor patients worldwide. Although surgery and chemotherapy have achieved dramatic achievement, the mortality remains high, resulting in the demand for new specific drug discovery. Disrupting ovarian cancer growth via histone deacetylase (HDAC) inhibition is a strategy for cancer therapy or prevention. In this work, we synthesized a novel pyridine derivative named compound H42 and investigated its anti-cancer activity in vivo and in vitro. We found that compound H42 inhibited ovarian cancer cell proliferation with IC50 values of 0.87 μM (SKOV3) and 5.4 μM (A2780). Further studies confirmed that compound H42 induced apoptosis, intracellular ROS production, and DNA damage. Moreover, compound H42 downregulated the expression of histone deacetylase 6 (HDAC6) with a distinct increase in the acetylation of α-tubulin and heat shock protein 90 (HSP90), followed by the degradation of cyclin D1, resulting in cell cycle arrest at the G0/G1 phase. Importantly, ectopic expression of HDAC6 induced deacetylation of HSP90 and α-tubulin, while HDAC6 knockdown upregulated the acetylation of HSP90 and α-tubulin. However, in the nude xenograft mouse study, compound H42 treatment can inhibit ovarian cancer growth without obvious toxicity. These findings indicated that compound H42 inhibited ovarian cancer cell proliferation through inducing cell cycle arrest at the G0/G1 phase via regulating HDAC6-mediated acetylation, suggesting compound H42 could serve as a lead compound for further development of ovarian cancer therapeutic agents.